Selected writings of Edgar Allan Poe - Poe, Edgar Allan, 1809-1849 (Houghton Mifflin, 1956)
The "Poe myth" notwithstanding, Edgar Allan Poe was neither a drunkard, a dope fiend, nor a rake, says Edward H. Davinson in his introduction to this abundant collection of Poe' s work: poetry, short stories, critical essays, amd complete Narrative of Arthur Gordon Pym. In addition to an analysis of thw century - old "Poe myth" , Professor Davidson provides a panetrating examination of Poe's work in each genre, a Selected Bibliography, a Poe Chronology, an index, and notes the texts.